Prognostic Value of Pretreatment Glasgow Prognostic Score/Modified Glasgow Prognostic Score in Ovarian Cancer: A Systematic Review and Meta-Analysis. (3rd July 2022) - Xu, Siyu; Song, Lei; Liu, Xiaoshi
Abstract: Purpose: : To explore prognostic value of pretreatment Glasgow prognostic score (GPS) and modified Glasgow prognostic score (mGPS) in ovarian cancer patients. Methods: : The PubMed, EMBASE (via OVID), and Web of Science databases were comprehensively searched for eligible studies. The hazard ratios (HRs) with 95% confidence intervals (CIs) were combined to evaluate the association of pretreatment GPS/mGPS with overall survival (OS) and progression-free survival (PFS) of ovarian cancer patients. STATA 12.0 version software was applied for statistical analysis. Results: : A total of eight retrospective studies involving 2260 were included into this systematic review and meta-analysis. The pooled results indicated that patients with elevated pretreatment GPS or mGPS had poorer OS (HR = 1.62, 95% CI: 1.38–1.91, P ＜.001) and PFS (HR = 1.40, 95% CI: 1.02–1.93, P = .039) than patients with pretreatment GPS or mGPS 0. Subgroup analysis based on the type of score (GPS or mGPS) and tumor stage for OS were also performed and the results were consistent with above findings. Conclusion: : Pretreatment GPS/mGPS might serve as promising prognostic indexes for ovarian cancer patients. More prospective studies with high-quality are needed to verify our findings.